A Komunikasi Politik Terbuka Partai: Pelaporan Dana Kampanye PKS Jawa Barat pada Pemilu 2019 - hayati, Neni Nur (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2022)
One of challenges brought by information transparency era is political communication. This study aims at revealing political communication strategy adopted by Partai Keadilan Sejahtera (PKS) of West Java, especially related to their efforts to build culture of transparency and accountability, especially related to political party funds during 2019 general election. This research employs qualitative descriptive methods with a case study. Informants are identified through a purposive sampling method. This research showed that in realizing information transparency and accountability, there are at least six elements involved. Those are: analysis of campaign fund report, transparency as a constitutional mandate and public rights, political communication channels and strategies, political practice in transparency of campaign fund report, and possible barriers to implement a culture of transparency and accountability. Having analyzed the case of PKS, it can be summarized that PKS’s case can be taken as a model which should be followed by other political parties in order to: a) open wider space for voters’ participation; and b) build a healthy party system in order to achieve a fair and free election.